Single-cell analysis reveals individual spore responses to simulated space vacuum - He, Lin; Wang, Shiwei; Cortesão, Marta; Wu, Muying; Moeller, Ralf; Setlow, Peter; Li, Yong-qing (My University, 2018)
Outer space is a challenging environment for all forms of life, and dormant spores of bacteria have been frequently used to study the survival of terrestrial life in a space journey. Previous work showed that outer space vacuum alone can kill bacterial spores. However, the responses and mechanisms of resistance of individual spores to space vacuum are unclear. Here, we examined spores’ molecular changes under simulated space vacuum (~10−5 Pa) using micro-Raman spectroscopy and found that this vacuum did not cause significant denaturation of spore protein. Then, live-cell microscopy was developed to investigate the temporal events during germination, outgrowth, and growth of individual Bacillus spores. The results showed that after exposure to simulated space vacuum for 10 days, viability of spores of two Bacillus species was reduced up to 35%, but all spores retained their large Ca2 +-dipicolinic acid depot. Some of the killed spores did not germinate, and the remaining germinated but did not proceed to vegetative growth. The vacuum treatment slowed spore germination, and changed average times of all major germination events. In addition, viable vacuum-treated spores exhibited much greater sensitivity than untreated spores to dry heat and hyperosmotic stress. Among spores’ resistance mechanisms to high vacuum, DNA-protective α/β−type small acid-soluble proteins, and non- homologous end joining and base excision repair of DNA played the most important roles, especially against multiple cycles of vacuum treatment. Overall, these results give new insight into individual spore’s responses to space vacuum and provide new techniques for microorganism analysis at the single-cell level.